Reconstruction of the legal basis for the policy on sinking foreign flag ships that commit fishing theft in Indonesia’s Exclusive Economic Zone - Widarmanto; Slamet Suhartono; Yovita Arie Mangesti; Erny Herlin Setyorini (Technium Social Sciences Journal, 2024)
Indonesia is a country whose territory consists of thousands of islands, most of which consist of waters and the rest are land. The ocean area is divided into territorial seas of 12 nautical miles, adjacent seas of 24 nautical miles, and an Exclusive Economic Zone of 200 nautical miles, measured from baseline of Indonesia. The total area of Indonesia reaches 7.7 million km2, with a sea area of 3.2 million km2, consisting of 2.8 million km2 of inland waters, and 0.3 million km2 of territorial waters, and 2.7 million km2 of the Indonesian Exclusive Economic Zone (ZEEI). In this study, the focus of attention is on fishing in ZEEI waters, which is carried out by foreign fishing vessels. The fact of fishing by foreign fishermen is indeed an unavoidable reality. From a legal perspective, fishing in the waters in ZEEI area is a criminal act or what is known as a fisheries crime. This is because fishing by foreign fishermen violates the provisions of fishing permits in Indonesia. Against these fisheries crimes, Indonesia as a sovereign country has the authority to supervise, secure, in the ZEEI area, and also has the authority to take action against foreign flag vessels that fish in the ZEEI area. The territory of Indonesia, most of which is approximately two-thirds ocean, contains enormous natural wealth, especially fishery resources. These fishery resources trigger foreign fishermen to commit fish theft, especially in the ZEEI area. As a sovereign country, Indonesia has full authority to enforce the law against criminal acts in the ZEEI area. Based on provisions of Article 69 paragraph (4) of Law No. 45 of 2009, Indonesia can impose sanctions on foreign-flagged fishing vessels by sinking vessels.